Conspiracy Thinking and Institutional Trust in Iceland: Implications for Vaccine Hesitancy During the COVID-19 Pandemic - Pawel Jan Wodnicki 1990- (2025)
COVID-19 pandemic highlighted the importance of vaccination campaigns in reducing the spread of pathogens and saving lives. In many countries, conspiracy theories and mistrust towards institutions posed a challenge to effectively employ the public health measures. This study explores the relationship between conspiracy thinking, institutional trust, and psychosocial well-being in the context of vaccine hesitancy in Iceland. Utilizing data from the 4th wave of nationwide survey, that took place in 2022, encompassing 11,409 participants, this research explores the prevalence and predictors of these constructs and their combined influence on vaccine hesitancy. Despite very high vaccine acceptance, the findings suggest that conspiracy thinking and distrust in institutions are significant predictors of vaccine hesitancy, while psychosocial well-being, including loneliness and mental fatigue, also plays a crucial role. The study further examines the demographic variations in conspiracy thinking and trust, revealing that younger individuals and those with lower education levels tend to report higher levels of conspiracy thinking, while higher education levels are associated with increased trust in institutions. The analysis also uncovers that loneliness and mental fatigue are positively associated with conspiracy thinking and negatively associated with trust in institutions. These findings shed light onto what psychosocial factors could be the targets of public health campaigns in high-trust settings like Iceland.